2015
DOI: 10.1371/journal.ppat.1004985
|View full text |Cite
|
Sign up to set email alerts
|

CR3 and Dectin-1 Collaborate in Macrophage Cytokine Response through Association on Lipid Rafts and Activation of Syk-JNK-AP-1 Pathway

Abstract: Collaboration between heterogeneous pattern recognition receptors (PRRs) leading to synergistic coordination of immune response is important for the host to fight against invading pathogens. Although complement receptor 3 (CR3) and Dectin-1 are major PRRs to detect fungi, crosstalk between these two receptors in antifungal immunity is largely undefined. Here we took advantage of Histoplasma capsulatum which is known to interact with both CR3 and Dectin-1 and specific particulate ligands to study the collaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 68 publications
5
78
0
1
Order By: Relevance
“…These data can be reconciled if the major role of dectin-1/CARD9 is to modulate NADPH oxidase and fungal killing via soluble mediators, rather than by cell-intrinsic activation. β2 integrins and TLR signaling can collaborate with dectin-1 to mount macrophage inflammatory responses to H. capsulatum and other fungi (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…These data can be reconciled if the major role of dectin-1/CARD9 is to modulate NADPH oxidase and fungal killing via soluble mediators, rather than by cell-intrinsic activation. β2 integrins and TLR signaling can collaborate with dectin-1 to mount macrophage inflammatory responses to H. capsulatum and other fungi (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…There have also been many studies describing synergistic or antagonistic intracellular signaling between PRR in antifungal immunity. Through association with lipid rafts, dectin-1 and CR3, for example, can collaboratively trigger macrophage IL-6 and TNF-α production via the Syk-JNK-AP1 pathway and subsequently induce host defense against disseminated histoplasmosis [79]. More recently, it has been suggested that dectin-1 can also interact with dectin-2 and trigger the Syk-JNK pathway to activate the NLRP3 inflammasome in response to H. capsulatum [80].…”
Section: Prr Crosstalkmentioning
confidence: 99%
“…Dectin 1 is a C-type lectin receptor found on macrophages, dendritic cells, and neutrophils that activates LAP in response to fungal challenge [9195]. The Dectin 1 carbohydrate recognition domain binds to fungal β-glucan, essentially a glucose polymer found in the cell walls of pathogenic bacteria and fungi [92].…”
Section: Lectin – Ligand Interactions Transmit Pro-autophagic Stimulimentioning
confidence: 99%
“…The Dectin 1 carbohydrate recognition domain binds to fungal β-glucan, essentially a glucose polymer found in the cell walls of pathogenic bacteria and fungi [92]. Recognition of this PAMP (pathogen associated molecular pattern) initiates phagocytosis as well as respiratory burst and inflammation for the purpose of eliminating the pathogen [91, 92, 94]. The offending pathogen is internalized in a single-membraned phagocytic vacuole or phagosome (distinct from an autophagosome), which undergoes a series of phenotypic changes to gain the necessary degradative potential.…”
Section: Lectin – Ligand Interactions Transmit Pro-autophagic Stimulimentioning
confidence: 99%
See 1 more Smart Citation